Ethylene Polymerization through Neutral Nickel Complexes Bearing Cyclic Imides - Hassan Arabi; Maryam Sadat Beheshti; Amin Manteghi (Advances in Polymer Technology)
The catalyst synthesis of salicylaldimine Ni(II) complexes with bulky imide moieties, ethylene polymerization, and characterization of synthesized polyethylenes are described in this paper. These Ni(II) complexes are designed to bear 2-aminobiphenyl and 4-tritylaniline. Results confirmed relatively high activity (up to 4×104 g PE mol Ni-1 h-1) of these catalysts in ethylene polymerization. Moreover, Ni(II) complexes demonstrated enhanced thermal stability, maintaining activity level up to 80°C. The generated polyethylenes possess moderate branching density and high melting temperatures. Less bulky 2-aminobiphenyl group resulted in higher branch content, while in Ni(II) complexes bearing 4-tritylaniline, more linear structure was observed. These semicrystalline polyethylenes showed mechanical properties similar to thermoplastics.